Neuropsychological Features of Children and Adolescents With Mitochondrial Disorders: A Descriptive Case Series - Riquin, Elise; Barth, Magalie; Le Nerzé, Thomas; Pasquini, Natwin; Prouteau, Clement; Colin, Estelle; Amati Bonneau, Patrizia; Procaccio, Vincent; Van Bogaert, Patrick; Duverger, Philippe; Bonneau, Dominique; Roy, Arnaud (Frontiers in Psychiatry, 2022)
Abstract Background: Mitochondrial disorders (MD) are a group of clinically heterogeneous genetic disorders resulting from dysfunction of the mitochondrial respiratory chain. Cognitive impairment is a common feature in adults with MD and psychiatric symptoms are associated with MD in up to 70% of the adult population. The aim of this study is to describe the neuropsychological profile in children and adolescents with MD. Methods: A sample of 12 children and adolescents was prospectively recruited between February 2019 and February 2020 in the Reference Center for Mitochondrial Disorders of Angers (France). Participants and their parents completed an anamnestic form to provide socio-demographic data and completed the WISC-V (Wechsler Intelligence Scale for Children, 5th edition) and the Parent and Teacher forms of the BRIEF (Behavior Rating Inventory of Executive Function). Results: In our sample, the mean IQ (Intellectual Quotient) score was 87.325.3. The score ranged from 52 to 120. Concerning executive functions, a significant global clinical complaint was found for parents (six times more than normal) and to a lesser extent, for teachers (among 3 to 4 times more). Levels of intelligence and executive functioning were globally linked in our cohort but dissociation remains a possibility. Conclusion: Our study shows that MD can lead to neuropsychological disorders in children and adolescents, especially regarding the intelligence quotient and the executive function. This highlights the need for regular neuropsychological assessments in individuals with developing brains, such as children and adolescents.